Co- and defect-rich carbon nanofiber films as a highly efficient electrocatalyst for oxygen reduction - Kim, Il To; Song, Myeong Jun; Shin, Seoyoon; Shin, Moo Whan (Applied surface science, 2018)
•Co- and defect-rich carbon nanofibers were prepared by a simple design strategy.•The catalyst showed enhanced oxygen reduction reaction (ORR) activity in base media.•High Co mass ratio, Co-pyridinic Nx, and C-N sites provide active sites for ORR.•The catalyst exhibited higher durability than Pt/C in base media. Many efforts are continuously devoted to developing high-efficiency, low-cost, and highly scalable oxygen reduction reaction (ORR) electrocatalysts to replace precious metal catalysts. Herein, we successfully synthesize Co- and defect-rich carbon nanofibers (CNFs) using an efficient heat treatment approach involving the pyrolysis of electrospun fibers at 370 °C under air. The heat treatment process produces Co-decorated CNFs with a high Co mass ratio, enriched pyridinic N, Co-pyridinic Nx clusters, and defect-rich carbon structures. The synergistic effects from composition and structural changes in the designed material increase the number of catalytically active sites for the ORR in an alkaline solution. The prepared Co- and defect-rich CNFs exhibit excellent ORR activities with a high ORR onset potential (0.954 V vs. RHE), a large reduction current density (4.426 mA cm−2 at 0.40 V), and a nearly four-electron pathway. The catalyst also exhibits a better long-term durability than commercial Pt/C catalysts. This study provides a novel hybrid material as an efficient ORR catalyst and important insight into the design strategy for CNF-based hybrid materials as electrochemical electrodes.